The effects of intra-cerebroventricular administered rocuronium on the central nervous system of rats and determination of its epileptic seizure-inducing dose - Mehmet Baykal (Brazilian Journal of Anesthesiology, 2017)
Background: The aim of this study was to investigate the effects of intracerebroventricularly administered rocuronium bromide on the central nervous system, determine the seizure threshold dose of rocuronium bromide in rats, and investigate the effects of rocuronium on the central nervous system at 1/5, 1/10, and 1/100 dilutions of the determined seizure threshold dose. Methods: A permanent cannula was placed in the lateral cerebral ventricle of the animals. The study was designed in two phases. In the first phase, the seizure threshold dose of rocuronium bromide was determined. In the second phase, Group R 1/5 (n = 6), Group 1/10 (n = 6), and Group 1/100 (n = 6) were formed using doses of 1/5, 1/10, and 1/100, respectively, of the obtained rocuronium bromide seizure threshold dose. Results: The rocuronium bromide seizure threshold value was found to be 0.056 ± 0.009 μmoL. The seizure threshold, as a function of the body weight of rats, was calculated as 0.286 μmoL/kg−1. A dose of 1/5 of the seizure threshold dose primarily caused splayed limbs, posturing, and tremors of the entire body, whereas the dose of 1/10 of the seizure threshold dose caused agitation and shivering. A dose of 1/100 of the seizure threshold dose was associated with decreased locomotor activity. Conclusions: This study showed that rocuronium bromide has dose-related deleterious effects on the central nervous system and can produce dose-dependent excitatory effects and seizures. Resumo: Justificativa: O objetivo deste estudo foi investigar os efeitos do brometo de rocurônio administrado intracerebroventricularmente sobre o sistema nervoso central, determinar a dose do limiar convulsivo de rocurônio em ratos e investigar os efeitos de rocurônio no sistema nervoso central em diluições de 1/5, 1/10 e 1/100 da dose do limiar convulsivo determinada. Métodos: Uma cânula permanente foi colocada no ventrículo lateral do cérebro dos animais. O estudo foi projetado em duas fases. Na primeira fase, a dose do limiar convulsivo do brometo de rocurônio foi determinada. Na segunda fase, o Grupo R 1/5 (n = 6), Grupo 1/10 (n = 6) e Grupo 1/100 (n = 6) foram formados usando doses de 1/5, 1/10 e 1/100, respectivamente, da dose do limiar convulsivo de brometo de rocurônio obtida. Resultados: Descobrimos que o valor do limiar convulsivo de brometo de rocurônio é 0,056 ± 0,009 μmoL. O limiar convulsivo, como uma função do peso corporal dos ratos, foi calculado como 0,286 μmoL/kg−1. Uma dose de 1/5 da dose do limiar convulsivo causou principalmente abertura postural dos membros e tremores em todo o corpo, enquanto uma dose de 1/10 da dose do limiar convulsivo causou agitação e tremores. Uma dose de 1/100 da dose do limiar convulsivo foi associada à diminuição da atividade locomotora. Conclusões: Este estudo mostrou que o brometo de rocurônio possui efeitos deletérios relacionados com a dose sobre o sistema nervoso central e pode produzir efeitos excitatórios dependentes da dose e convulsões. Keywords: Rocuronium, Seizure, Central nervous system, Rat, Palavras-chave: Rocurônio, Convulsão, Sistema nervoso central, Rato